Optical amplification of single-photon polarization qubit using weak measurement. (1st December 2020) - Zhao, Ruitong; Guo, Jianjun; Cheng, Lianglun
Abstract: Single-photon amplification can be used to overcome the photon loss in long-distance quantum communication. However, the trade-off of success probability and amplification gain should be further improved. We propose a single-photon polarization qubit amplification using weak measurement. The polarization qubit can be amplified by the pre- and post-selection of the single-photon meter state weakly coupling with the input state. The success probability does not decrease asymptotically to 0 with increasing amplification gain in the presented proposal, and is higher than that in entanglement-based schemes, without coincidence detection required. Our proposal is feasible in current technology, and helpful for near-future quantum communication.